1997
DOI: 10.1111/1468-005x.00018
|View full text |Cite
|
Sign up to set email alerts
|

E‐mail as a Weapon in an Industrial Dispute

Abstract: The case study on which this article is based describes a two-and-ahalf month long strike of Israeli academic staff members. During the strike, e-mail was used as the major means of communication between the strikers. Analysis of the e-mail messages demonstrates that e-mail served as a secret weapon, enabling the strikers to succeed in what was presumed to be a hopeless battle.nations (eg., avoidance of e-mail adoption

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 3 publications
1
25
0
Order By: Relevance
“…Second, e‐communications can be used for alliance building within unions, between unions and between unions and other parties relevant to the dispute (Martinez Lucio ; Pliskin et al . ). Third, the possibility of real‐time communication exchanges allows negotiators and members to remain in regular contact at each stage of the negotiations/dispute process, thereby enhancing solidarity (Pliskin et al .…”
Section: Three Points Of Departurementioning
confidence: 97%
See 2 more Smart Citations
“…Second, e‐communications can be used for alliance building within unions, between unions and between unions and other parties relevant to the dispute (Martinez Lucio ; Pliskin et al . ). Third, the possibility of real‐time communication exchanges allows negotiators and members to remain in regular contact at each stage of the negotiations/dispute process, thereby enhancing solidarity (Pliskin et al .…”
Section: Three Points Of Departurementioning
confidence: 97%
“…The data thus confirm that the virtual branch websites may enhance solidarity during industrial disputes (Pliskin et al . ) as their use facilitates real‐time communications and enhances the capacity to mobilize at short notice. Given the small proportion of members that reported in the surveys that they were aware of the virtual branch websites mentioned above (26.8 per cent in 2011), it is apparent that the vast majority of members aware of the virtual branch websites used them at branches that were in dispute.…”
Section: The Participation Of Members In the Virtual Branchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholarship on union Internet use has highlighted how ICT‐based communications present opportunities to organised labour, such as increasing solidarity during an industrial dispute (Pliskin et al ., 1997), accommodating diverse, distributed or conflicting voices within the membership (Carter et al ., 2003; Greene et al ., 2003) and extending the labour movement's global reach (Lee, 2004). Looking at how ICTs can improve union services and enhance organising drives, Diamond and Freeman (2002) argue that the Internet potentially ‘bridges the gap between an increasingly heterogeneous and individualistic work‐force and the collective activity and solidarity that lies at the heart of trade unionism’ (p. 570).…”
Section: Literature Reviewmentioning
confidence: 99%
“…She concluded that -knowledge displayed itself as a collective resource; non-hierarchical bonds were strengthened; individuals were augmented by their participation in group life; work and play, productivity and learning, seemed ever more inseparable.‖ (Zuboff, 1988, p. 386). Pliskin (et al, 1997) showed how e-mail was used by Israeli academic staff members on strike to enhance cohesion. Lee (1997) gives scores of examples of Internet use by unions around the world, such as on-line strike newspapers, on-line discussion groups for members and interunion communication (see Taylor, 1996).…”
Section: Online Support For Offline Communitiesmentioning
confidence: 99%